An estimation of the economic value of an air quality improvement program in Santiago, Chile - Figueroa, Eugenio; Firinguetti, Luis; Rogat, Jorge (Estudios de Economía, 2016)
There is no doubt regarding the negative effects of air pollution on human health, economic property and the environment. The almost fie million inhabitants living in Santiago, Chile, are exposed to high levels of air contamination, especially during winter time when the level of pollution is at its worst. In this paper, a hedonic price model is used to first, estimate the effect of air pollution on house prices in Santiago and second, to estimate the willingness to pay (WTP) for a program that reduces air contamination by 50 percent. The data consists of 992 observations containing market prices for houses and their characteristics. The average WTP for the air quality improvement program was estimated in 567,000 (US 1,626), and the aggregated WTP for Santiago in almost 600 billion pesos (US 1.7 billion).